2006
DOI: 10.1242/jeb.02112
|View full text |Cite
|
Sign up to set email alerts
|

How much stress do researchers inflict on their study animals? A case study using a scincid lizard, Eulamprus heatwolei

Abstract: SUMMARY Research on live vertebrates is regulated by ethics committees, who prohibit `excessively stressful' procedures. That judgment is based on intuition – a notoriously unreliable criterion when dealing with animals phylogenetically distant from humans. To objectively evaluate the stress imposed by research practices, we measured plasma corticosterone levels in lizards (Eulamprus heatwolei Wells & Wellington, Scincidae). Some procedures (handling and measuring, toe-clipping for identific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
143
3
3

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 219 publications
(157 citation statements)
references
References 29 publications
8
143
3
3
Order By: Relevance
“…Langkilde and Shine (2006) determined that corticosterone levels in southern water skinks that were transferred into novel environments were higher than animals that had been handled and measured, had toes clipped, or had been exposed to predator scent. Some of the reptiles in the Healesville Sanctuary reptile house were rotated through different enclosures, and there was constant rearrangement of cage furnishings.…”
Section: Discussionmentioning
confidence: 99%
“…Langkilde and Shine (2006) determined that corticosterone levels in southern water skinks that were transferred into novel environments were higher than animals that had been handled and measured, had toes clipped, or had been exposed to predator scent. Some of the reptiles in the Healesville Sanctuary reptile house were rotated through different enclosures, and there was constant rearrangement of cage furnishings.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies show that often, our evaluations of stressful methods, based on intuition, can be notoriously unreliable (e.g. Langkilde and Shine 2006), and suggest using the increase in GCs as a more objective marker of physiological stress in vertebrates (e.g. Romero 2004).…”
Section: Impact Of Research Protocolmentioning
confidence: 99%
“…Romero 2004). Using this method, Langkilde and Shine (2006) compared diVerent research procedures used commonly in lizards, and found that some superWcially trivial manipulations such as housing the animal in an unfamiliar enclosure was very stressful for the animal, while a often criticized method (toeclipping) was less stressful than the technique frequently recommended to replace it on ethical grounds (microchip implantation).…”
Section: Impact Of Research Protocolmentioning
confidence: 99%
“…Capture and handling, often required to apply marking, may also affect normal behavior of an individual, at least in the short‐term (Rodda et al. 1988; Langkilde and Shine 2006). Such impacts are undesirable, particularly for threatened or rare species (Bradfield 2004), but also when the goal of research is to observe natural population processes and behavior with minimal interference.…”
Section: Introductionmentioning
confidence: 99%